Data-only contention-based grant-free multiple access for 5G mMTC - Shizhuang ZHANG; Zhifeng YUAN; Weimin LI (Dianxin kexue)
For contention-based grant-free access, reference signal collision would restrict the performance. A data-only contention-based grant-free scheme was considered, where the blind detection receiver does not depend on reference signal to detect users’ information by fully exploiting the characteristics of the data itself, so the limitation from reference signal collision can be avoided, leading to a much higher traffic load. On the other hand, traffic load was further limited by inter-cell interference. Data-only signal does not include cell-specific processing, each cell station could detect all the received signals, including those from adjacent cells, through advanced blind detection receiver. This actually played the role of traditional inter-cell interference cancellation and therefore can achieve a better performance gain. And it would not introduce too much additional complexity.